2003
DOI: 10.2337/diacare.26.12.3219
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in a Native Canadian Population Experiencing Rapid Epidemiological Transition

Abstract: OBJECTIVE -Adiponectin is emerging as an important protein in the etiology of obesity and related metabolic disorders. The objectives of this study were to determine cross-sectional and prospective associations of adiponectin concentration with adiposity, type 2 diabetes, and cardiovascular disease (CVD) risk factors in a population-based study of Native Canadians, a group experiencing dramatic increases in diabetes and CVD.RESEARCH DESIGN AND METHODS -During the 1993-1995 baseline survey, samples for glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0
1

Year Published

2004
2004
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
6
30
0
1
Order By: Relevance
“…Treatment with octreotide (or Sandostatin) is accompanied by an increase in total body fat [36]. The serum adiponectin level has been shown to vary inversely with total body fat in large population-based studies [38]. BMI does not distinguish between fat mass and lean body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with octreotide (or Sandostatin) is accompanied by an increase in total body fat [36]. The serum adiponectin level has been shown to vary inversely with total body fat in large population-based studies [38]. BMI does not distinguish between fat mass and lean body mass.…”
Section: Discussionmentioning
confidence: 99%
“…19,40 In these analyses, two (Indians) and three (Native Canadians) factors has been shown with adiponectin loading with the lipids factors. 19,40 Adiponectin clustered with HDL-cholesterol (positive correlation) and triglycerides (inverse correlation), In particular, the positive association with HDL-cholesterol may explain the anti-atherogenetic properties of adiponectin, which may reflect the insulin-sensitizing effects of adiponectin. 40 It is noteworthy, that adiponectin also clustered together with fasting insulin and waist circumference in women in the present study.…”
Section: -14mentioning
confidence: 99%
“…19 Most factor analyses of the metabolic syndrome in different populations have identified between three to four distinct factors including obesity, dyslipidemia, hyperglycemia and hypertension. 38,39 In the present study based on an elderly…”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation
“…In the First Nation population, obesity is more prevalent among men than women, but the prevalence of metabolic syndrome and type 2 diabetes appears to be greater for women than men, suggesting that First Nation women may be more insulin resistant than their male counterparts (6,8). Studies in Canadian Aboriginal populations have found elevated adipocytokines such as tumor necrosis factor (TNF)-␣, C-reactive protein (CRP), and leptin (9,10), whereas adiponectin levels were found to be reduced (11). In some of these studies, percent body fat determined by electric impedance was reported to be elevated.…”
mentioning
confidence: 99%